KINERJA PERBANKAN SEBELUM DAN SELAMA PANDEMI COVID-19: PENGUJIAN TERHADAP DAMPAK KEBIJAKAN COUNTERCYCLICAL INDONESIA - Sulistianingsih, Sulistianingsih (Badan Penerbit Universitas Muria Kudus, 2025)
This study examines the Indonesian banking performance before and during the COVID-19 pandemic with focus on the impact of the government's countercyclical policies as an economic stimulus. The research population is commercial banks listed on the IDX, using purposive sampling technique and secondary data from Publication Reports for the 2017-2022 period using the Wilcoxon test. The findings show that there are significant differences between banking LDR, NIM, CAR and there are no significant differences between NPL, ROA before and during the COVID-19 pandemic. The empirical results from this research can be used by bankers, financial regulator and the government to design further policies in handling the impact of the COVID-19 pandemic and post-pandemic which can strengthen financial stability, especially in the banking sector in Indonesia.